Feeling excluded and not having anyone to talk to: Qualitative study of interpersonal relationships following a cancer diagnosis in a sibling. (October 2019) - Toft, Teolinda; Alfonsson, Sven; Hovén, Emma; Carlsson, Tommy
Abstract: Purpose: To explore experiences related to interpersonal relationships following a cancer diagnosis in a sibling. Methods: Respondents (n = 7 females) were recruited by means of convenience sampling during a camp for children affected by childhood cancer and their siblings. Data from children and adolescents with a sibling diagnosed with cancer was collected through individual face-to-face interviews and analyzed using systematic text condensation. Results: Two categories portrayed the experiences related to interpersonal relationships following a cancer diagnosis in a sibling. Feeling excluded while wanting to maintain a relationship with their ill sibling and be involved in the care portrayed that trying to be involved in the care of their ill sibling was a stressful and difficult experience, since they were simultaneously expected to also manage household chores and attend school. Feeling stigmatized and exposed in social contexts while needing an allowing space to talk about their experiences portrayed the emotional difficulties evoked by social situations and behaviors of others, which left respondents feeling exposed and mistreated. Having the possibility to talk about their experiences and receiving social support was described as essential in order to cope with the situation. Conclusions: Health professionals need to take into consideration the emotional difficulties and vulnerable situation that children and adolescents who have a sibling diagnosed with cancer are at risk of experiencing. Stigmatization and social exposure present a risk of psychological distress. Having an allowing space to communicate feelings and experiences is desired. Interventions may be necessary to help these individuals psychologically cope. Highlights: Social exclusion and stigmatization can cause considerable psychological distress. Demands in everyday life may inhibit sufficient involvement in the care of their sibling. Social support among peers have the potential to ease psychological distress.